STUDIES ON THE UTILIZATION OF SPENT CATALYST USED IN OIL REFINERY (Biological Sciences - PJSIR, 2004)
Enormous amount of the spent cobalt-molybdenum/alumina catalyst, used for the hydrodesulphurization process in the oil refineries, is locally available for its safe disposal. Studies were undertaken on this spent catalyst for the extraction of valuable metals contained in it. Its chemical evaluation indicated the presence of CoO 3.43%, MoO3 14.50%, Al2O3 79.67% and SiO2 2.40%. In view of the high prices of cobalt and molybdenum in the international market, the research and development work were mainly concentrated on the extraction of these metals. Leaching studies undertaken on the samples indicated the optimum recovery of cobalt up to 96% and 96.5% for molybdenum.